2006
DOI: 10.1121/1.2372455
|View full text |Cite
|
Sign up to set email alerts
|

The kurtosis metric as an adjunct to energy in the prediction of trauma from continuous, nonGaussian noise exposures

Abstract: Data from an earlier study [Hamernik et al. (2003). J. Acoust. Soc. Am. 114, 386-395] were consistent in showing that, for equivalent energy [Leq= 100 dB(A)] and spectra, exposure to a continuous, nonGaussian (nonG) noise could produce substantially greater hearing and sensory cell loss in the chinchilla model than a Gaussian (G) noise exposure and that the statistical metric, kurtosis, computed on the amplitude distribution of the noise could order the extent of the trauma. This paper extends these results to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…The results shown in Figure 1 yielded a typical DRR for both groups with the complex noiseexposed group shifted to the left and with a steeper slope relative to G noise-exposed subjects. Although the number of subjects in this study is limited, the results suggest that, as with the animal model data, complex non-G noise exposure is more hazardous to hearing than is an energy equivalent continuous G noise (Hamernik et al 2003;Qiu et al 2006Qiu et al , 2007Davis et al 2009).…”
Section: Cumulative Noise Exposure and The Kurtosis Metricmentioning
confidence: 76%
See 1 more Smart Citation
“…The results shown in Figure 1 yielded a typical DRR for both groups with the complex noiseexposed group shifted to the left and with a steeper slope relative to G noise-exposed subjects. Although the number of subjects in this study is limited, the results suggest that, as with the animal model data, complex non-G noise exposure is more hazardous to hearing than is an energy equivalent continuous G noise (Hamernik et al 2003;Qiu et al 2006Qiu et al , 2007Davis et al 2009).…”
Section: Cumulative Noise Exposure and The Kurtosis Metricmentioning
confidence: 76%
“…Recent results from animal experiments (Hamernik et al 2003;Qiu et al 2006Qiu et al , 2007Davis et al 2009) have shown that the kurtosis (␤) of the amplitude distribution, a statistical metric that is sensitive to the peak and temporal characteristics of a noise, could order the extent of hearing and sensory cell loss from a variety of complex noise exposures. They showed that for a fixed energy level, the noise-induced trauma increased as the kurtosis increased.…”
Section: Introductionmentioning
confidence: 99%
“…A given NIPTS may be achieved by using a wide variety of noise exposure levels and durations. Up to some level that depends on noise type (kurtotic versus Gaussian), noise level and duration can be traded to similar effect, as long as total energy is constant (Qiu et al 2006). However, for any type of noise, there exists a level where Bmicroinjury^and metabolic fatigue will give way to overt tearing of the reticular lamina.…”
Section: Lesioning the Mouse Inner Earmentioning
confidence: 99%
“…Of the 11 identified depletion target proteins in NT OF, all were quantified at 90% reduced expression following EMD; 32 upregulated proteins, with twofold or more increased expression, were detected following EMD. Four of these showed a 100-fold increase in expression: 1) a 78-kDa glucose-regulated protein; this protein is an ER chaperone which regulates protein folding; it is known to be upregulated during embryonic cardiac development [22], and highly upregulated in a variety of cancer specimens, including breast cancer, lung cancer, liver cancer and prostate cancer [23][24][25]; 2) 14-3-3 epsilon protein is a regulatory factor, involved in signal transduction activity; it's expression level is known to be upregulated in head and neck squamous cell carcinoma [26], Alzheimer's disease and Down syndrome patients; 3) leukotriene A-4 hydrolase is a bifunctional zinc enzyme with epoxide hydrolase and aminopeptidase activities; this low-abundance OF protein was first visualized in 2-DE following TD OF, as we previously published [10], and here it presented a higher expression level following EMD; it is known to increase significantly in human atherosclerotic plaque [27]; in addition, its overexpression seems to be an early event in esophageal adenocarcinogenesis and it has been suggested as a potential target for the chemoprevention of esophageal adenocarcinogenesis [28]; 4) vitamin D-binding (DBP) protein is a carrier protein used for solubilization and transport of vitamin D and its metabolites in the serum; many studies have discussed the link between DBP phenotypes and susceptibility or resistance to osteoporosis, Graves' disease [29], Hashimoto's thyroiditis [30], diabetes [31][32][33] COPD [34,35], AIDS [36], multiple sclerosis [37], sarcoidosis [38] and rheumatic fever [30,39].…”
Section: Discussionmentioning
confidence: 63%